2006
DOI: 10.1002/bio.899
|View full text |Cite
|
Sign up to set email alerts
|

Particle‐induced myeloperoxidase release in serially diluted whole blood quantifies the number and the phagocytic activity of blood neutrophils and opsonization capacity of plasma

Abstract: Luminol-amplified chemiluminescence (CL) from phagocytes has previously been shown to be almost completely dependent on the release of myeloperoxidase (MPO) from azurophilic granules. We measured the luminol-amplified chemiluminescence response (WBCL) by using serially diluted whole blood. In these experiments, non-opsonized and serum-opsonized zymosan (NWBCL and OWBCL, respectively) were used concurrently as phagocytosable particles. We found two whole-blood dilution ranges with clinical significance: first, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…Interestingly, NOB induced WBCL response never reached the same magnitude of WBCL induced by OB as observed with trout ( Fig. 1D) or human phagocytes [25]. Under similar measurement conditions with trout blood phagocytes, the CL response induced with NOB reaches the magnitude of OB at a final blood dilution of 6.0 ml ml ÿ1 showing that at this blood concentration the amount of plasma factors (w0.3% of plasma concentration) is sufficient to fully opsonise NOB in situ.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Interestingly, NOB induced WBCL response never reached the same magnitude of WBCL induced by OB as observed with trout ( Fig. 1D) or human phagocytes [25]. Under similar measurement conditions with trout blood phagocytes, the CL response induced with NOB reaches the magnitude of OB at a final blood dilution of 6.0 ml ml ÿ1 showing that at this blood concentration the amount of plasma factors (w0.3% of plasma concentration) is sufficient to fully opsonise NOB in situ.…”
Section: Discussionsupporting
confidence: 57%
“…The RB activities of blood phagocytes were stimulated with various bacterial strains (see Section 2) at a final blood dilution of 1:650 in the presence of 0.4% of gelatin and 0.3% of cod serum at 15 C. Heparin always gave at least 25% higher CL response compared to EDTA or citrate indicating that cod blood phagocytes were activated in the heparin (Fig. 4A), as also observed by us with human phagocytes [25]. In addition, the concentration of EDTA in tubes is w6 mM when the tube is filled with blood.…”
Section: The Effect Of Anticoagulants and Bacterial Strain On Rb Actimentioning
confidence: 55%
“…The induction of ROS production in leukocytes caused by the A. actinomycetemcomitans D7S wild-type and ΔhofQ mutant cells was studied using a luminol-amplified chemiluminescence experiment [51] with some modifications. Briefly, triplicate reactions were prepared in a white 96-well plate (Greiner Bio-One, #9,502,887) in a total volume of 250 µl: 100 µl of bacterial suspension (1.25 × 10 7 CFU), 10 µl of luminol (10 mM in borate buffer), 3 µl of human plasma/serum, 50 µl of human leukocytes (1/3 dilution) and 87 µl of gHBSS (1 mg/ml gelatin in HBSS: 1 mM CaCl 2 , 5 mM KCl, 0.4 mM KH 2 PO 4 , 0.5 mM MgCl 2 ∙6H 2 O, 0.4 mM MgSO 4 ∙7H 2 O, 140 mM NaCl, 4 mM NaHCO 3 , 0.3 mM Na 2 HPO 4 , and 6 mM glucose).…”
Section: Methodsmentioning
confidence: 99%
“…A homogenous bacterial suspension was prepared from three-day plate cultures of the A. actinomycetemcomitans D7S wild-type or ΔhofQ mutant strains. Plasma/serum was collected from 3 ml of (EDTA-coagulated) whole blood after centrifugation (1000 × g, 10 min, RT), and leukocytes were freshly isolated from 1 ml of (EDTA-coagulated) whole blood following a protocol by Lilius and Nuutila [51]. Measurement of chemiluminescence (every 2 min for 200 min; Victor [3] multilabel plate reader (Perkin Elmer) or Hidex Sense microplate reader (Hidex)) was started immediately after leukocytes were added to the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…The resultant CL emission is directly linked to the activity of neutrophils. Previous studies have shown that the signal is due to the release of myeloperoxidase (MPO) from the azurophilic granules of the phagocytes (Lilius and Nuutila, 2006).…”
Section: [ ( F I G _ 3 ) T D $ F I G ]mentioning
confidence: 99%